Generation of Flp-intm-ready DG44 and Lec 3.2.8.1 CHO cell lines for quick and easy constitutive protein expression - DC Soler; AE Young; A Vahedi-Faridi; TS McCormick (BioTechniques)
The well-characterized cell line Chinese hamster ovary (CHO) has been used to produce numerous biopharmaceuticals and is an important tool for basic research. However, introducing foreign DNA into specially modified CHO cells such as DG44 and Lec 3.2.8.1 can sometimes be an arduous process. Here we show that the Flp-intm plasmid can be modified to produce a fluorescent tracer protein tag (mCherrytm) as a fusion reporter, to allow for the rapid selection of single-cell sorted, isogenic Flp-intm-ready DG44 and Lec 3.2.8.1 cell lines. These two cell lines are stable and viable and may be useful for applications such as antibody production and crystallographic studies. Here we provide key details on how the modified pFRT/CherryZeo plasmid may be used to incorporate Flp-intm technology into virtually any desired target cell line in a fast, safe and reliable manner.